EFEKTIVITAS EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav.) SEBAGAI REPELEN TERHADAP NYAMUK Aedes aegypti - Mayang Rustia Anggraini Putri; Erida Wydiamala; Lisda Hayatie (Homeostasis, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. One effective option to prevent the transmission of the disease is by avoiding the bite of the Aedes aegypti mosquito by using a repellent-type insecticide. The use of chemical insecticides widely circulated in the market often has negative effects, such as irritation to the skin. Red betel leaf contains several active compounds that may act as contact poisons and are effective as repellents. The purpose of this study was to test the effectiveness of ethanol extract of red betel leaf against Aedes aegypti mosquitoes. This study was an true experimental post-test only with a control group design, consisting of 4 concentrations of ethanolic extract of red betel leaf (12.5%, 25%, 50%, 100%), DEET 15% K(+), and aquades K(-) with four replications. Serial concentrations ethanol extract of red betel leaf K(+), and K(-) were applied to the back skin of mice exposed to mosquitoes for 5 minutes for every minute. The concentration of 100% at every minute had no significant difference with the positive control (p>0.05). The conclusions from this research were red betel leaf ethanol extract with concentrations of 12.5%, 25%, 50%, and 100% was effective as a mosquito repellent Aedes aegypti, and red betel leaf ethanol extract with a concentration of 100% was equivalent to 15% DEET